Aortic Dissection in a Healthy Male Athlete: A Unique Case with Comprehensive Literature Review - Balraj Singh; Jennifer M. Treece; Ghulam Murtaza; Samit Bhatheja; Steven J. Lavine; Timir K. Paul (Case Reports in Cardiology)
A young otherwise healthy 27-year-old male who has been using anabolic steroids for a long time developed Type I aortic dissection associated with heavy weightlifting. The patient did not have a recent history of trauma to the chest, no history of hypertension, and no illicit drug use. He presented with severe chest pain radiating to back and syncopal event with exertion. Initial vitals were significant for blood pressure of 80/50 mmHg, pulse of 80 beats per minute, respirations of 24 per minute, and oxygen saturation of 92% on room air. Physical exam was significant for elevated jugular venous pressure, muffled heart sounds, and cold extremities with diminished pulses in upper and absent pulses in lower extremities. Bedside echocardiogram showed aortic root dilatation and cardiac tamponade. STAT computed tomography (CT) scan of chest revealed dissection of ascending aorta. Cardiothoracic surgery was consulted and patient underwent successful repair of ascending aorta. Hemodynamic stress of weightlifting can predispose to aortic dissection. Aortic dissection is a rare but often catastrophic condition if not diagnosed and managed acutely. Although rare, aortic dissection needs to be in the differential when a young weightlifter presents with chest pain as a delay in diagnosis may be fatal.